Pharmacokinetics of Anticancer Drugs Used in Treatment of Older Adults With Colorectal Cancer: A Systematic Review. Issue 5 (October 2019) - Shafiei, Mohsen; Yoon, Robert; McLachlan, Andrew; Boddy, Alan; Beale, Philip; Blinman, Prunella
Abstract : Purpose: Older adults with cancer experience more toxicity from anticancer therapy, possibly because of age-related changes in the pharmacokinetic (PK) profile of anticancer drugs. We aimed to evaluate studies investigating the effect of aging on the PK of anticancer therapies used in the treatment of colorectal cancer (CRC). Methods: A systematic literature search of EMBASE and PubMed was performed to find eligible studies that assessed the effect of age on the PK of anticancer therapies used in the treatment of CRC. Results: The 21 eligible studies included 17 prospective studies and 4 pooled analyses of prospective studies. Of these, PK of 5-fluorouracil (5-FU) was determined in 7 studies, oxaliplatin in 2 studies, capecitabine in 3 studies, irinotecan in 4 studies, bevacizumab in 1 study, cetuximab in 3 studies, and panitumumab in 1 study. Studies included a median of 44 patients and had varying definitions for older adults: 65 years or older (3 studies), older than 70 years (3 studies), or older than 75 years (1 study). Increasing age significantly affected the PK parameters of irinotecan with a 7%–8% reduction in CL ( P < 0.001) for every 10 years in patients older than 60 years and an increase in area under the curve (r = 0.44, P = 0.007) and Cmax (r = 0.42, P = 0.009). Conclusions: Older age mainly influences PK of irinotecan and, to some extent, that of capecitabine, 5-FU, and panitumumab, but there is limited evidence for age-related changes in PK of other anticancer therapies used in the management of older adults with CRC. Factors other than PK may be responsible for the greater toxicity of these agents experienced by older adults.